Postpartum contraception: efficacy and safety - N M Nazarova; V N Prilepskaya; M E Nekrasova (IP Berlin A.V., 2018)
Timely and reasonable selection of methods of contraception after childbirth from the standpoint of safety for the mother and the child, in addition to preventing unwanted pregnancy, preserves the reproductive health of the woman. When choosing a method of contraception in the postpartum period, it is necessary to take into account the impact of the method on lactation, the condition of the mother and child. Prenatal counseling allows to increase the commitment of women selected method of postpartum contraception.